THE INFLUENCE OF PEER INTERACTION, HOME AND SCHOOL ON SELF ESTEEM OF ADOLESCENTS (Journal of Guidance and Counselling Studies, 2022)
This study explored the contribution of peer interaction, Home and school on self-esteem of Adolescents in Aba metropolis. Two hundred and ninety SS2 students (Males 147, Females 143) randomly selected from six secondary schools with about fifty respondents selected by simple random sampling from each school participated in this study. The age distribution of respondents is between 14-19years with a mean age of 16.37 years and a standard deviation of 1.57. The students were administered Hare self-esteem scale. Data obtained were analyzed using t-test statistic for independent samples. Results obtained show that gender and type of school attended by students does not influence their self-esteem whereas peer interaction, home and school were found to significantly impact on adolescent’s self-esteem. The mean score of the participants fall below the norm, therefore the results were discussed in terms of recommendation for action and therapy.
Keywords: Contribution; Peer Interaction; Home; School; Self Esteem; Adolescents